2016
DOI: 10.1080/10426507.2016.1192627
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriostatic activities ofN-substituted tris-thioureas bearing amino acid and aniline substituents

Abstract: A series of tri-substituted thiourea derivatives were synthesized by the reaction of 1,3,5-triacetylbenzoyl isothiocyanate with aminoacids and aniline derivatives. All thiourea derivatives were characterized by FT-IR, 1 H and 13 C NMR spectroscopy. Antibacterial activities against wild-type Escherichia coli American Type Culture Collection 8739 were determined by use of Downloaded by [University of Nebraska, Lincoln] at 07:04 01 June 2016 ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 2 the turbidimetric method to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Compounds a-b showed binding free energy of −4.5 kcal/mol and −4.7 kcal/mol, respectively. Based on the importance properties of the aromatic group in earlier studies [6][7][8], the optimisation study via molecular docking was carried out to evaluate the binding free energy of a-b in comparison to the predicted phenyl thiourea a-b. The presence of another aromatic group in a-b demonstrated for a higher binding affinity with the free energy of −5.9 kcal/mol and −6.3 kcal/mol, respectively.…”
Section: Molecular Docking Design and Optimisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds a-b showed binding free energy of −4.5 kcal/mol and −4.7 kcal/mol, respectively. Based on the importance properties of the aromatic group in earlier studies [6][7][8], the optimisation study via molecular docking was carried out to evaluate the binding free energy of a-b in comparison to the predicted phenyl thiourea a-b. The presence of another aromatic group in a-b demonstrated for a higher binding affinity with the free energy of −5.9 kcal/mol and −6.3 kcal/mol, respectively.…”
Section: Molecular Docking Design and Optimisationmentioning
confidence: 99%
“…Multisubstituted thioureas have gained more interest among researchers due to the increase of their pharmaceutical properties. Our recent studies on thiourea reported that compounds that consist of more than one thiourea moiety possess better antimicrobial activities [6][7][8]. It was due to the presence of more active sites of thiourea moieties containing C=S, C=O, and N-H groups, which are easily protonated under acidic condition and interacted with the carboxyl and phosphate groups of the bacterial surfaces, thus enhancing the biological activities [7].…”
Section: Introductionmentioning
confidence: 99%